Microstructural evolution and characterisation of interfacial phases in Al2O3/Ag–Cu–Ti/Al2O3 braze joints. (1st September 2015) - Ali, Majed; Knowles, Kevin M.; Mallinson, Phillip M.; Fernie, John A.
Abstract: Alumina ceramics with different levels of purity have been joined to themselves using an active braze alloy (ABA) Ag–35.3Cu–1.8Ti wt.% and brazing cycles that peak at temperatures between 815 °C and 875 °C for 2 to 300 min. The microstructures of the joints have been studied using scanning electron microscopy, transmission electron microscopy, and energy dispersive X-ray spectroscopy. A limited number of joints prepared with the ABA Ag–26.7Cu–4.5Ti wt.% have also been studied. In terms of characterising the interfacial phases, efforts were made to understand the interfacial reactions, and to determine the influence of various brazing parameters, such as the peak temperature ( T p ) and time at T p ( τ ), on the microstructure. In addition, the extent to which impurities in the alumina affect the interfacial microstructure has been determined. Ti3 Cu3 O has been identified as the main product of the reactions at the ABA/alumina interfaces. At the shortest joining time used, this phase was observed in the form of a micron-size continuous layer in contact with the ABA, alongside a nanometre-size layer on the alumina that was mostly composed of γ-TiO grains. Occasionally, single grains of Ti3 O2 were observed in the thin layer on alumina. In the joints prepared with Ag–35.3Cu–1.8Ti wt.%, the interfacial structure evolved considerably with joining time, eventually leading to a high degree of inhomogeneity across the length of the joint at the highest T p . The level of purity of alumina was not found to affect the overall interfacial microstructure, which is attributed to the formation of various solid solutions. It is suggested that Ti3 Cu3 O forms initially on the alumina. Diffusion of Ti occurs subsequently to form titanium oxide at the Ti3 Cu3 O/alumina interface.